Exploring circular economy concept in affordable housing project: a case study on the flexzhouse IBS housing business model - Mohd Noor, Mohd Zairul (Pertubuhan Akitek Malaysia, 2019)
The idea of a circular economy (CE) has become more popular nowadays in the manufacturing industry. However, the concept of a circular economy in the housing industry or built environment is still at infancy. Therefore, this article explores circular economy concept in affordable housing project through ‘flexZhouse’ IBS housing business model. This article reported part of the thesis entitled: flexZhouse: a new business model for affordable housing in Malaysia. This article posits as the first study to suggest integrating housing industry with the circular economy. Therefore, it fills a gap in the knowledge about IBS housing. This article, which pursued the identified problems by developing a new business model (BM), will benefit the government of Malaysia, as it formulated a solution for affordable housing schemes and created an alternative business model for the housing industry.